Generation of Land Remote Sensing Satellites Conceptual Design Based on Regard to Required Efficiency Indices. (2015) - Kirilin, Alexander; Akhmetov, Ravil'; Kurenkov, Vladimir; Stratilatov, Nikolay; Abrashkin, Valeriy; Kucherov, Alexander; Safronov, Sergey; Yakishchik, Artyom
Abstract: Approaches to the choice of main design parameters and conceptual design of land remote sensing satellites are considered. The approach based on providing required efficiency indices of the spacecraft has number of advantages. It allows forming such a sequence of design procedures, which provides a choice of the basic design parameters and formation of conceptual design with a minimum number of iterations. Main approach items are discussed.